Invisible Hands, Russian Experience, and Social Science : Approaches to Understanding Systemic Failure. - Hedlund, Stefan (Cambridge University Press, 2011)
This book investigates cases in which national and international activities have gone massively wrong, entailing seriously negative consequences.